Chemical Vapor Deposition of Ionic Liquids for the Fabrication of Ionogel Films and Patterns. Issue 49 (1st October 2021) - Obst, Martin; Arnauts, Giel; Cruz, Alexander John; Calderon Gonzalez, Maider; Marcoen, Kristof; Hauffman, Tom; Ameloot, Rob
Abstract: Film deposition and high‐resolution patterning of ionic liquids (ILs) remain a challenge, despite a broad range of applications that would benefit from this type of processing. Here, we demonstrate for the first time the chemical vapor deposition (CVD) of ILs. The IL‐CVD method is based on the formation of a non‐volatile IL through the reaction of two vaporized precursors. Ionogel micropatterns can be easily obtained via the combination of IL‐CVD and standard photolithography, and the resulting microdrop arrays can be used as microreactors. The IL‐CVD approach will facilitate leveraging the properties of ILs in a range of applications and microfabricated devices. Abstract : Chemical vapor deposition of an ionic liquid allows the formation of ionogel thin films and microdrops in high resolution. The non‐volatile ionic liquid is formed on a surface by reaction of two non‐volatile precursors. A broad range of applications will benefit from this new "IL‐CVD" approach, which enables the fabrication of microdevices.